CLINICAL OUTCOMES OF PATIENTS WITH ENDOPHTHALMITIS AFTER DEXAMETHASONE INTRAVITREAL IMPLANT. Issue 10 (October 2022) - Samuelson, Annika G.; Nahar, Ankur; Patel, Samir N.; Mahmoudzadeh, Raziyeh; Salabati, Mirataollah; Yu-Chuan Kang, Eugene; Hinkle, John W.; Soares, Rebecca R.; Kuriyan, Ajay E.; Garg, Sunir J.
Abstract : Purpose: To report a case series of endophthalmitis associated with intravitreal dexamethasone injections in a single practice and to discuss the clinical findings and visual outcomes of each case. Methods: All endophthalmitis cases following intravitreal dexamethasone injections performed from January 1, 2014 to October 20, 2020 were identified using Wills Eye/MidAtlantic billing records. The diagnosis, clinical information, and microbiology were confirmed for each case. Data were analyzed using Excel (Microsoft Excel, Redmond, WA). Results: Four cases of endophthalmitis were identified from 3, 925 intravitreal dexamethasone injections in a single practice and one case was referred from an outside institution, resulting in an incidence of 0.102% (1 in 981 injections). Mean age was 82.3 years (range, 63–88 years) with a mean of 11.3 intravitreal dexamethasone injections performed (range, 2–30 injections) before endophthalmitis. Cases presented with endophthalmitis a mean (SD) of 3.6 (1.64) days after causative injection. Three cases grew gram-positive organisms. All patients responded to intravitreal antibiotics. Mean logarithm of the minimal angle of resolution visual acuity at causative injection, endophthalmitis presentation, 3 months, and last follow-up was 0.44 (20/55), 2.22 (20/3, 319), 1.18 (20/303), and 1.46 (20/577), respectively. Conclusion: Endophthalmitis following intravitreal steroid injections may occur more frequently than other intravitreal injections. Dexamethasone-attributed endophthalmitis remains uncommon, and prompt intravitreal antibiotic treatment seems to be effective in this series.